The learning of Mandarin to early childhood at Ar-rahmah islamic education school - Ayuningtias, Niza; Pujiono, Mhd.; Nasution, Vivi Adryani; Nasution, Ely Hayati (Talenta Publisher, 2019)
Mandarin has been used as one of the subjects in Indonesia's schools including kindergarten/PAUD. However, many obstacles faced by the school. The lack of training and teaching staff of Mandarin for early childhood education moved the hearts of the USU Community Service Team to conduct Early Childhood Mandarin Learning training for pre- school educators in one of the Kindergarten schools in Medan, namely RA Ar -Rahmah. The method of this activity is intensive training with a blend of theory and practice as well as discussion and performance of the training results. Teaching Mandarin to educators is carried out with the principle of